THE ANTIOXIDANT AND ANTIANGIOGENIC EFFECTS OF DIETARY SUPPLEMENT OF NIGELLA SATIVA CRUDE OIL ON BREAST TUMOR IN BALB/C MICE - Sima Bahramian; Mohammad Reza Bigdeli; Bahram Rasoulian (Lorestan University of Medical Sciences, 2017)
Background and Aim: Cancer embraces a vast range of diseases including that of the breast and is triggered by various factors such as reactive species of oxygen. Angiogenesis, then, aids the cancerous mass to meet its needs and develop further. Nigella sativa L. (NS), traditionally cultivated and consumed in the Middle East, has long been appreciated for its medicinal benefits. In this study, we aimed to look into its antioxidant and anti-angiogenic effects on breast tumor in BALB/c mice. Materials and Methods: 3 groups of BALB/c mice, respectively received 1, 2 and 4 ml/kg/day of NS crude oil via gavaging for 4 months before breast tumor transplantation, while the control mice were gavaged with distilled water. Then tumor volume, the activity of antioxidant enzymes, the amounts of VEGF and endostatin were studied to examine NS crude oil's impact against breast tumor. Results and Conclusions: Our findings revealed that the mice pretreated with 4 ml/kg/day of NS oil had significantly smaller tumor volumes, higher SOD and CAT activity, reduced VEGF and increased endostatin amounts. So, we came to this that Nigella sativa crude oil seems to inhibit breast tumor growth in part by improving the activity of antioxidant enzymes and in part by interfering with angiogenesis. More studies are, yet, required to better illuminate its other mechanisms of involvement.